THE EFFECT OF THINK PAIR SHARE TECHNIQUE ON STUDENTS’ ACHIEVEMENT IN SPEAKING - Dessy Putri Utami and Sumarsih (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2016)
This study aims to find out whether students’ achievement taught by using ThinkPair Share Technique has significant effect than taught Dictation Technique inSpeaking. The research was conducted by Experimental research using in twogroups. They are experimental used Think Pair Share Technique and Control usedDictation Technique. The subject of this were the students of SMAN 6 Medanclass X-2 and X-3 consisted of 38 students for each class. The data was takenfrom Speaking test. After analyzing the data, it was found that the value of t-obswas 3.982 with degree of freedom (df) 38 at the level of significance p (0.05) =2.024. It means that t-obs is higher than t-table. It was found that studentsachievement in Speaking taught by Think Pair Share Technique has significanteffect than Dictation Technique.